Kualitas Kompos dari Sampah Organik Rumah Tangga Menggunakan Variasi Jenis Mikroorganisme Lokal - Enida Fatmalia; Dini Yuliansari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
One of the effects of plant fertility is the addition of compost which contains bioactivators. One of the bioactivators that can be used in the composting process is to use MOL (Local Microorganisms). MOL can be made from various types of organik waste that is around us, such as MOL from Banana Stem, Used/Stale Rice, Used/Rotten Fruits, and can also use EM4 purchased at a farm shop. The different types of MOL materials added to the composting will also affect the quality of the compost produced based on SNI 19-7030-2004. Therefore, it is necessary to test the quality of the compost with the addition of different MOLs. This research is experimental research with a qualitative approach. This research was conducted in the Workshop and STTL Mataram Biology and Chemistry Laboratory. The results showed that the four composts that have been researched, there are several parameters that are still not in accordance with the Good Compost Quality Standards based on SNI 19-7030-2004, included the color parameters in the compost with the addition of MOL. there are leaf pieces that have not been completely decomposed, the chemical parameter of COrganik in the compost with the addition of MOL of used rice that exceeds the maximum level of 32.74%, and the level of C/N-Ratio in the compost with the addition of MOL banana stem which is still below the minimum level of 22,7% only. Compost that has good quality and according with SNI 19-7030-2004 is compost with the addition of MOL from EM4.